PENGARUH INSENTIF DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN LAHAT - Sephy Husnainy (Jurnal Manajemen dan Bisnis, 2021)
This study aims to examine Effect of Incentives and Work Environment Against Job Performance Employees At the Office of the Regional Development Planning Board Lahat regency . The sampling technique used is the census method , ie the entire population studied by distributing questionnaires to the employees of the Office of Regional Development Planning Board Lahat which numbered 60 people . The data analysis in this research using descriptive analysis and testing techniques Infrensial data used in this study is the normality test , F test ( ANOVA ) and t test in order to prove the hypothesis of the study . Simple Regression Analysis showed from the regression equation is Y = 2,149 + 0,862 + 0,109X1 X2 or Job Performance = 2,149 + Incentives 0109 + 0862 Work For these three variables can be seen constants = 0.116 , Incentives = 0.011 and Working Environment = 0.000 . This means that employees working in the Office of Regional Development Planning Board (Bappeda ) Lahat Incentives variable significant effect on employee job performance of Regional Development Planning Board Lahat ( for figures of significance < 0.05 ) , while the working environment positive effect and significant impact on Employee Job Performance Regional Development Planning Board Lahat ( because the numbers Significance < 0.05 )